Extended Pharmacopeial Characterization of Surfactant Aerosols Generated by a Customized eFlow Neos Nebulizer Delivered through Neonatal Nasal Prongs - Federico Bianco; Elena Pasini; Marcello Nutini; Xabier Murgia; Carolin Stoeckl; Martin Schlun; Uwe Hetzer; Sauro Bonelli; Marta Lombardini; Ilaria Milesi; Marisa Pertile; Stephan Minocchieri; et al. (Pharmaceutics, 2020)
The delivery of nebulized medications to preterm infants during Non-Invasive Ventilation (NIV) remains an unmet clinical need. In this regard, the effective delivery of nebulized surfactant has been particularly investigated in preclinical and clinical studies. In this work, we investigated the feasibility of delivering nebulized surfactant through various commercially available nasal prong types. We first performed a compendial characterization of surfactant aerosols generated by the eFlow Neos nebulizer, customized to be used in neonates, determining the amount of surfactant delivered by the device as well as the aerodynamic characteristics of surfactant aerosols. Additionally, we extended the compendial characterization by testing the effect of different nasal prong types on the estimated lung dose using a realistic Continuous Positive Airway Pressure (CPAP) circuit that included a cast of the upper airways of a preterm neonate. The compendial characterization of surfactant aerosols delivered through different nasal prongs achieved relatively high delivered surfactant doses (in the range 63–74% of the nominal dose), with aerodynamic characteristics displaying mass median aerodynamic diameters ranging between 2.52 and 2.81 µm. Nevertheless, when using a representative in vitro setup mimicking NIV in a clinical setting, significant differences were observed in terms of the estimated lung dose accounting for up to two-fold differences (from 10% to 20% estimated lung deposition of the nominal dose) depending on the chosen nasal prong type. Considering that surfactant lung deposition rates are correlated with therapeutic efficacy, this study points out the relevance of choosing the appropriate NIV interface to maximize the lung dose of nebulized medications.